The Trade Relations between India and China - Jose, Jackson (2015)
The aim of this research is to evaluate the issues and problems of transportation faced by China and India through air and road, and to have a deeper understanding about the problems faced by ports in China and India, concerning the activities of trade. This research dissertation will focus on analysing and studying the challenges and issues faced by both the Nations in trading with each other. The specific challenges which will be investigated in this dissertation are the transportation of products and the issues of supply chain and interaction. The main aim of the research is focused to evaluate the key issues and challenges related to the transportation infrastructure in India and China through road and air. Thus it will be helpful to have a detailed understanding of how the activities of trade are being conducted between the two nations. Different aspects will be covered that will include the collection of secondary data for presenting the literature review and for the purpose of further analysis. Based on this secondary data collected and analysed, key points of conclusion will be drafted.